Biomass and Carbon Stock of Trees in Amchang Wildlife Sanctuary, Assam, North Eastern India - Yumnam, J.Y. (Indian Forester, 2023)
Forest in and around the urban areas are recognised as a major sequester of Carbon and store huge quantity of Carbon in their biomass. However, these forest patches are facing destruction and degradation due to the expanding urban limits. For efficient Carbon mitigation, it is essential to precisely quantify Carbon stock of forests. This study was taken up to quantify biomass and Carbon stock of trees growing in Amchang Wildlife Sanctuary, which is situated on the eastern side of Guwahati city (Kamrup metropolitan) Assam, Northeast India. Extensive field survey was undertaken and sampling of all trees was made using random quadrat method. Altogether 50 quadrats of 10x10 m2 were laid down for the study. Biomass and Carbon stock of trees were calculated by using allometric formula. The total above ground biomass (AGB), below ground biomass (BGB), total biomass (TB) and Carbon stock (TCS) of the sanctuary were 307.60 Mg ha-1, 79.97 Mg ha-1, 387.57 Mg ha-1 and 193.79 Mg C ha-1 respectively. Tree density and total basal cover (TBC) showed strong positive correlation with TCS (R2 = 0.70 and 0.68 respectively). However, wood density and diameter of the trees showed weak positive correlation with TCS (R2 = 0.02 and 0.12 respectively) in the study site. The present study revealed that Amchang Wildlife Sanctuary, Assam, Northeast India has high Carbon stock.